Constructing a research model for liver regeneration by using hepatocyte-like organoid derived from human pluripotent stem cells - WANG Chenxi, YANG Shuchun, JIA Yuyan, HUANG Yue (Jichu yixue yu linchuang)
Objective To construct an in vitro research model for studying human liver regeneration based on human pluripotent stem cells (hPSCs)-derived hepatocyte-like organoid (HLO). Methods The hPSCs-derived HLO was obtained by inducing differentiation and the regeneration model after liver injury was constructed by adding acetaminophen (APAP) at fixed time points in HLO culture conditions to simulate acute liver injury. Subsequently, HLO with catenin/cadherin-associated protein beta 1(CTNNB1) knockout, a key gene regulating liver regeneration, was constructed using CRISPR/Cas9 gene editing technology, and regeneration experiments with APAP injury were performed. HLO as a model for liver regeneration studies was further evaluated by morphological observation, RT-qPCR, Western blot and pathological analysis. Results Morphology evidence as well as expres-sion of marker genes showed that hPSCs-derived HLO was able to initiate a post-injury regeneration response after APAP treatment. CTNNB1-deficient HLO showed delayed recovery in dimension and down-regulated or delayed expression of related genes during post-injury regeneration as compared to control HLO. Conclusions A HLO-based hPSCs-derived human liver regeneration model is successfully constructed, which can be used for gene function studies during liver regeneration.